The Influence Of Health Promotion On Controlling Risk Factors For Non-Communicable Diseases - Sahabuddin Sahabuddin; Dewi Nashrulloh; Baso Witman Adiaksa; Yanti Mustarin; Andi Kamal M. Sallo (International Journal of Health Sciences, 2026)
Non-communicable diseases (NCDs) are the leading cause of death and morbidity worldwide, including in Indonesia. NCD risk factors such as smoking, unhealthy diet, lack of physical activity, and excessive alcohol consumption are strongly influenced by individual behavior. Health promotion is an important strategy in efforts to control NCD risk factors by improving public knowledge, attitudes, and behavior. This study aims to determine the effect of health promotion on controlling NCD risk factors. The study used an observational analytical design with a cross-sectional approach. The study sample consisted of 150 respondents selected using a purposive sampling technique. Data were collected through a health promotion questionnaire and a NCD risk factor questionnaire, then analyzed using the Chi-Square test and odds ratio analysis. The results showed that health promotion had a significant effect on controlling NCD risk factors (p < 0.05). It was concluded that intensive and sustainable health promotion plays an important role in controlling NCD risk factors.